Assessing the Value of Seasonal Climate Forecasts on Farm-level Corn Production through Simulation Modeling - Kathrina G. Gonzales; Canesio D. Predo; Rosalina G. de Guzman; Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 2009)
Rainfall variability greatly influences corn production. Thus, an accurate forecast is potentially of value to the farmers because it could help them decide whether to grow their corn now or to delay it for the next cropping opportunity. A decision tree analysis was applied in estimating the value of seasonal climate forecast (SCF) information for corn farmers in Isabela. The study aims to estimate the value of SCF to agricultural decisionmakers under climate uncertainty. Historical climatic data of Isabela from 1951 to 2006 from PAGASA and crop management practices of farmers were used in the Decision Support System for Agrotechnology Transfer (DSSAT) to test the potential impact of climate change on corn. The approach is developed for a more accurate SCF and to be able to simulate corn yields for wet and dry seasons under different climatic conditions. While SCF may potentially affect a number of decisions including crop management practices, fertilizer inputs, and variety selection, the focus of the study was on the effect of climate on corn production. Improving SCF will enhance rainfed corn farmers' decisionmaking capacity to minimize losses brought about by variable climate conditions.
Keywords: 330; seasonal climate forecast (SCF); decision tree analysis; climate uncertainty; Decision Support System for Agrotechnology Transfer (DSSAT)